A Brief Review of the Types of Validity and Reliability of scales in Medical Research - Sajjad Bahariniya; Mohammad Ezatiasar; Farzan Madadizadeh (Shahid Sadoughi University of Medical Sciences, 2021)
Dear Editor in Chief Reliability and validity are concepts used to evaluate the quality of  psychometric properties of a scale in medical research. Reliability is related to reproducibility, and validity is related to the accuracy of a scale. It is important to check reliability and validity when using a scale or questionnaire. The present study provides a brief overview of the types of validity and reliability in medical research.